Answers

2015-11-20T21:00:45+08:00
-2(x-3)=7-(x+2)
-2x+6=7-x+2
-2x+x=7+2-6
-x=3
-x/-1=3/-1
x=-3

4(x-1)=3(X+1)
4X-4=3X+3
4X-3X=3+4
X=7
0
  • Brainly User
2015-11-20T22:59:55+08:00
-2(x-3) = 7 - (x + 2)
-2x + 6 = 7 + (-x - 2)   ⇒ In subtracting polynomials, change the sign of
                                     each
  term of the subtrahend, then proceed to
                                     addition

-2x + 6 = 7 - x - 2
-2x + 6 = 5 - x
-2x + x = 5 - 6
-x = -1
-1(-x = -1) -1
x = 1

4(x - 1) = 3 (x + 1)
4x - 4 = 3x + 3
4x - 3x = 3 + 4
x = 7

0